Recent Advances in C-C and C-N Bond Forming Reactions Catalysed by Polystyrene-Supported Copper Complexes - Drabina, Pavel; Svoboda, Jan; Sedlák, Miloš (Molecules (Basel, Switzerland), 2017)
This present mini-review covers recently published results on Cu(I) and Cu(II) complexes immobilized on polystyrene carriers, which are used as heterogeneous, eco-friendly reusable catalysts applied for carbon-carbon and carbon-nitrogen forming reactions. Recent advances and trends in this area are demonstrated in the examples of oxidative homocoupling of terminal alkynes, the synthesis of propargylamines, nitroaldolization reactions, azide alkyne cycloaddition, N-arylation of nitrogen containing compounds, aza-Michael additions, asymmetric Friedel-Crafts reactions, asymmetric Mukaiyama aldol reactions, and asymmetric 1,3-dipolar cycloaddition of azomethine ylides. The type of polystyrene matrix used for the immobilization of complexes is discussed in this paper, and particularly, the efficiency of the catalysts from the point of view of the overall reaction yield, and possible enantioselectivity and potential reusing, is reviewed.
Keywords: polystyrene; polystyreny; C–C bond forming reaction; měď; copper complexes; Carbon; Catalysis; uhlík; Polystyrenes; Nitrogen; supported catalyst; dusík; recyclable catalyst; katalýza; C–N bond forming reaction; Copper